Size-Dependent Nest Site Choice by Cavity-Dwelling Ants - Joan M. Herbers; Valerie Banschbac (Psyche: A Journal of Entomology)
Nest site choice by cavity-dwelling ants of north temperate deciduous forests was studied at two sites in the northeastern United States. The two numerically dominant ant species in these communities, Myrmica punctivenris and Leptothorax longispinosus, chose different cavity sizes in experiments employing artificial nest sites. These preferences for different cavity sizes should prove useful for studies involving experimental manipulation of cavity-dwelling ant species.